A pilot analysis: can the Bulgarian split-squat potentiate sprint acceleration in strength-trained men? - Lockie, R. G.; Orjalo, A.; Moreno, M. (Facta Universitatis: Series Physical Education and Sport, 2017)
This study determined whether a five repetition-maximum Bulgarian split-squat (5RM BSS) could potentiate a 0-5, 0-10, and 0-20 m (meter) sprint performance. Seven men were assessed in the 5RM BSS (a linear position transducer measured peak power [PP] and force [PF] for each leg), and completed two post activation potentiation (PAP) sessions. One session involved a control condition (CC) of 4 minutes (min) rest; the other the 5RM BSS. Participants were assessed in baseline sprints, and sprints of 15 seconds, 2, 4, 8, 12, and 16 min post-PAP intervention. A repeated measures ANOVA (p < 0.05) calculated significant changes in sprint times. The best potentiated time for each interval was also compared to the baseline. Spearman`s correlations (r; p < 0.05) calculated relationships between absolute and relative strength, PP and PF, with percent potentiation in sprint times. The BSS did not potentiate speed at any time, although there was great individual variation. The best 0-5 m time was significantly different from the baseline (p = 0.022), with no differences between PAP conditions. Significant correlations were found between strength and sprint potentiation at 16 min for the 0-5 m interval, and at 8 min and the best times for the 0-20 m interval (r = -0.786 to -0.893). There were correlations between PP and PF for each leg with sprint potentiation from 2-12 min across all intervals (r = -0.786 to -0.964). Stronger individuals who generate greater PP and PF in a 5RM BSS will be more likely to potentiate 20-m sprint performance.